2009
DOI: 10.1177/0022034509343101
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast Mechanoresponses on Ti with Different Surface Topographies

Abstract: During implant healing, mechanical force is transmitted to osteogenic cells via implant surfaces with various topographies. This study tested a hypothesis that osteoblasts respond to mechanical stimulation differently on titanium with different surface topographies. Rat bone-marrow-derived osteoblastic cells were cultured on titanium disks with machined or acid-etched surfaces. A loading session consisted of a 3-minute application of a 10- or 20-mum-amplitude vibration. Alkaline phosphatase activity and gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 21 publications
4
16
0
3
Order By: Relevance
“…Therefore, the relationship between early and late cellular responses is very important for current research. It is believed with certainly that osteogenic differentiation can be shown that ALP has an activating effect on the surface modification of materials [15][16][17][18][19][20][21][22][23][24][25][26] . There is also evidence that surface modification of nanostructures can increase calcium deposition 15,16,18,20,26) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the relationship between early and late cellular responses is very important for current research. It is believed with certainly that osteogenic differentiation can be shown that ALP has an activating effect on the surface modification of materials [15][16][17][18][19][20][21][22][23][24][25][26] . There is also evidence that surface modification of nanostructures can increase calcium deposition 15,16,18,20,26) .…”
Section: Introductionmentioning
confidence: 99%
“…1 A variety of materials have been investigated as bone replacements, such as conventional titanium and its alloys, micron grain sized ceramics (eg, hydroxylapatite or HA) and nanostructured hydrogels (eg, poly-lactic-co-glycolic acid or PLGA). [2][3][4][5] However, current conventional implants suffer from limited lifetimes, often failing before the end of a patient's natural life expectancy. 6,7 For example, today's orthopedic implants usually have insufficient initial bone growth on their surface and/or poor maintenance of healthy juxtaposed bone over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…As reações bioquímicas induzidas pelo estímulo mecânico atuam em nível celular e podem causar inibição da apoptose, aumento da proliferação celular, alteração na migração celular, entre outros efeitos [81].…”
Section: Marcador De Sinalização Celular -Proteína Citoplasmática Tirunclassified
“…Este estímulo é transmitido por toda a célula através de uma complexa rede que conecta a membrana plasmática ao núcleo da célula [81].…”
Section: Marcador De Sinalização Celular -Proteína Citoplasmática Tirunclassified
See 1 more Smart Citation